Effectiveness of homeopathic complexes on gastrointestinal nematodes in sheep - Ubiratã Mariano de Souza; Mayara Isaías Vargas; Ricardo Lopes Dias da Costa; Rodrigo Giglioti; Cecília José Veríssimo (Boletim de Indústria Animal, 2022)
Gastrointestinal nematodeos are one of the biggest obstacles to sheep farming, requiring integrated control and prophylaxis measures. The indiscriminate use of synthetic anthelmintics can cause parasitic resistance. We hypothesized that pharmacological alternatives, such as homeopathy, can contribute to the control of nematodeos in sheep. This study thus evaluated the efficacy of three homeopathic complexes (HCs) for the control of worms in naturally infected sheep. The research was carried out at the sheep unit of the Instituto de Zootecnia (IZ) in Nova Odessa (SP), from April 18 to June 19, 2022. Ten grams of HCs (powder form) was mixed in 500 grams of concentrate and given daily to each animal in a common trough in a paddock with 10 animals. Each paddock corresponded to treatments 1, 2 and 3 (with HCs) and 4 (control, concentrate without HCs), totaling 40 ewes. The complexes were formulated with five homeopathic medicaments in sucrose as vehicle, namely: Spigelia anthelmia 9 CH (CH = centesimal hahnemannian), Arsenicum album 11 CH , Kali phosphoricum 15 CH, Cina 9 CH and Apis mellifica 15 CH, adding Ora Pro Nobis 6 CH (T1 treatment), Ferrum metallicum 6 CH (T2 treatment), or Ora Pro Nobis and Ferrum metallicum in equal parts (T3 treatment). The homeopathic substances were chosen in accordance with the guidebook “Homeopathic and Pharmacological Medical Material”, by Demarque, Jouanny, Poitevin and Saint-Jean. The animals underwent an adaptation period of 15 days before receiving the CHs, after which they were observed on three occasions, every 15 days, to measure the following parameters: number of Trichostrongylidae (T) and Strongylidae (S) eggs per gram of feces, Famacha®, hematocrit, body condition score, and weight. Four animals (1 T1, 2 T3 and 1 T4) left the experiment for different reasons (previous illness or parturition during the experiment). The efficacy of the treatments was calculated using the Reso 2.0 program. This program calculates the effectiveness based on the number of eggs found in the control and treated animals on each evaluation day. The results of the effectiveness of the treatments for T1 were 6%, 71% and 72% efficacy for T, and 78%, 20% and 81% for S, at 15, 30 and 45 days of administration, respectively. In T2, efficacy values considering T eggs were 0%, 69% and 79%, and for S, 97%, 46% and 44% at 15, 30 and 45 days, respectively. In T3, no efficacy was observed in relation to T (0% in all observations), but the efficacy values for S were 63%, 100% and 75% at 15, 30 and 45 days of product ingestion. It is noteworthy that the effectiveness of homeopathic medicines occurred in a situation in which all groups were losing weight. We concluded that daily HCs supply contributed to the control of gastrointestinal nematodes in sheep.